Framing the Debate: Pharmaceutical Patents and the Right to Health under International Law (International Journal of Scientific Research and Management (IJSRM), 2025)
The Global struggle for equitable access to essential medicines has brought renewed focus to the tension between pharmaceutical patents and the right to health. This paper examines the interaction between the international legal framework, particularly the TRIPS agreement, and human rights obligations enshrined in instruments such as the ICESCR. It explores the extent to which patent law is designed to reward innovation. May inadvertently restrict the availability of affordable medicines for people in need in low- and middle-income countries. Drawing on legal analysis, recent global health emergencies, such as COVID-19, have responded. The paper argues that structural reform is necessary to realign global intellectual property governance with human rights norms, emphasizing the principles of equality, transparency, and shared responsibility. The analysis underscores the necessity for a collaborative legal and ethical framework that prioritizes public health without compromising the innovation ecosystem. Ultimately, the paper contributes to a growing body of scholarship advocating for a rights-based balance between intellectual property protection and universal access to health.